TINDAK TUTUR DIREKTIF GURU DALAM PROSES PEMBELAJARAN BAHASA INDONESIA KELAS VIII SMPN 1 TANJUNG RAYA - Zilfia Ardhiany Yolanda; Herlin Triana; Tressyalina; Ena Noveria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Directive speech acts are closely linked to teachers’ professional competence because, in the learning process, teachers’ language skills significantly influence the effectiveness of classroom communication. The purpose of this study is to describe the forms of directive speech acts and the speaking strategies of Indonesian language teachers in the learning process. This study employs a qualitative approach using a descriptive method. The results of the study indicate that teachers use five forms of directive speech acts: asking, commanding, requesting, suggesting, and challenging. Of these five forms of directive speech acts, the one most frequently used by teachers is asking, with 84 instances of speech. In addition, this study also examined the speech strategies used by teachers during instruction; the dominant strategy used by teachers was the “Straightforward Speech Without Small Talk” (BTTB) strategy, which was found in 49 speech data points. Thus, it can be concluded that Indonesian language teachers in Grade 8 at SMPN 1 Tanjung Raya use five types of directive speech acts and four speech strategies in Indonesian language instruction.